-18=-2x-3(-2x-10)

Simple and best practice solution for -18=-2x-3(-2x-10) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -18=-2x-3(-2x-10) equation:


Simplifying
-18 = -2x + -3(-2x + -10)

Reorder the terms:
-18 = -2x + -3(-10 + -2x)
-18 = -2x + (-10 * -3 + -2x * -3)
-18 = -2x + (30 + 6x)

Reorder the terms:
-18 = 30 + -2x + 6x

Combine like terms: -2x + 6x = 4x
-18 = 30 + 4x

Solving
-18 = 30 + 4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4x' to each side of the equation.
-18 + -4x = 30 + 4x + -4x

Combine like terms: 4x + -4x = 0
-18 + -4x = 30 + 0
-18 + -4x = 30

Add '18' to each side of the equation.
-18 + 18 + -4x = 30 + 18

Combine like terms: -18 + 18 = 0
0 + -4x = 30 + 18
-4x = 30 + 18

Combine like terms: 30 + 18 = 48
-4x = 48

Divide each side by '-4'.
x = -12

Simplifying
x = -12

See similar equations:

| 2xy-8y+3x-12=0 | | R^2+16=10r | | 4x+6+x=5+9x+9 | | -7X^2+44X-50=-4X^2+29X-32 | | 3*x=568 | | 14=-2x-4(-4x+14) | | log[log(3x-5)]=0 | | 48=4x+5(x-3) | | x^2+y^2-16x+10y-3=0 | | x^2-4xy-5y^2=0 | | graphx^2-4xy-5y^2=0 | | x+x-19=87 | | 4h-(3h-10)=2h-(8-5h)+(3h-18) | | 2x^3+3x^2-32x+15=0 | | 9f+(-2f+6)=3f+(5-6f)-(-5f-18) | | 6w-(4w-7)=5w-(4-9w)+(-4w+35) | | 2x^2+6-24=x^2+1x | | 5X^2-47X+70=3X^2-31X+46 | | 5(9c+7)=4(4c-4)+6 | | 7+4+x=22 | | p^3+9p^2+14p=0 | | 8(8y+6)=4(8x-1)+1 | | 3(8m+4)=8(6m-1)+5 | | m+1+8=10 | | 4X^2+25X+21=2X^2+15X+13 | | 2(2x-5)=3x-1 | | -3(x-2)=-1(x-26) | | 9x-7y+2z=6 | | (x+3)=5(x-3) | | 10(4+x)=50 | | 6-7x=70-35x | | 12z-(3z-1)-2z-35=z+58 |

Equations solver categories